2022
DOI: 10.1002/cam4.4780
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication use in parents of survivors of adolescent cancer: A register‐based cohort study

Abstract: Background The aim was to investigate psychotropic medication use in parents of survivors of adolescent cancer from the acute post‐diagnostic phase and up to 2 years following the cancer diagnosis. Methods This study had a nationwide register‐based cohort design comparing psychotropic medication use in parents of adolescent survivors of cancer ( n = 2323) to use in parents of cancer‐free controls ( n = 20,868). Cox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the context of childhood cancer, the outcome is often uncertain and many parents recognize the possibility of their child's death at the time of diagnosis. We have previously shown that parents of survivors of adolescent cancer (excluding bereaved parents) are at increased risk of use of anxiolytics and sedatives in the immediate post‐diagnostic phase 24 . The results of the present study might thus reflect parents' reactions to the initial cancer diagnosis as well.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In the context of childhood cancer, the outcome is often uncertain and many parents recognize the possibility of their child's death at the time of diagnosis. We have previously shown that parents of survivors of adolescent cancer (excluding bereaved parents) are at increased risk of use of anxiolytics and sedatives in the immediate post‐diagnostic phase 24 . The results of the present study might thus reflect parents' reactions to the initial cancer diagnosis as well.…”
Section: Discussionmentioning
confidence: 63%
“…We have previously shown that parents of survivors of adolescent cancer (excluding bereaved parents) are at increased risk of use of anxiolytics and sedatives in the immediate post‐diagnostic phase. 24 The results of the present study might thus reflect parents' reactions to the initial cancer diagnosis as well. Aligned with this, anticipatory grief responses have been reported by parents of children newly diagnosed with cancer.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous research shows that a high proportion of parents of children with cancer report distress, such as anxiety, post‐traumatic stress symptoms, worry, and nervousness 2,3 . The burden of care often places a strain on the well‐being of parents, and, accordingly, an increased risk of psychotropic medication use has been reported, especially among mothers 4,5 . In addition, having a child with cancer may negatively impact levels of income and employment status, which can put further strain on the family 6 .…”
Section: Introductionmentioning
confidence: 99%